Can Cytoreductive Nephrectomy Improve Outcomes of Nivolumab Treatment in Patients with Metastatic Clear-Cell Renal Carcinoma? - Birol Ocak; Ahmet Bilgehan Sahin; Ismail Ertürk; Mustafa Korkmaz; Dilek Erdem; Umut Cakıroglu; Mustafa Karaca; Ahmet Dirican; Omer Fatih Olmez; Sabin Goktas Aydın; Ali Gökyer; Ahmet Kücükarda; et al. (Current Oncology)
Background: This study aimed to investigate the effect of cytoreductive nephrectomy (CN) on the survival outcomes of nivolumab used as a subsequent therapy after the failure of at least one anti-vascular endothelial growth factor (VEGF) agent in patients with metastatic clear-cell renal-cell carcinoma (ccRCC). Methods: We included 106 de novo metastatic ccRCC patients who received nivolumab after progression on at least one anti-VEGF agent. Multivariate Cox regression analysis was performed to investigate the factors affecting survival in patients receiving nivolumab. Results: Of the 106 de novo metastatic ccRCC patients, 83 (78.3%) underwent CN. There were no statistical differences between the two groups in terms of age, gender, Eastern Cooperative Oncology Group (ECOG) score, tumor size, International Metastatic RCC Database Consortium (IMDC) risk group, number of previous treatment lines, first-line anti-VEGF therapy, or metastasis sites (p = 0.137, p = 0.608, p = 0.100, p = 0.376, p = 0.185, p = 0.776, p = 0.350, and p = 0.608, respectively). The patients who received nivolumab with CN had a longer time to treatment discontinuation (TTD) [14.5 months, 95% confidence interval (CI): 8.6–20.3] than did those without CN 6.7 months (95% CI: 3.9–9.5) (p = 0.001). The median overall survival (OS) was 22.7 months (95% CI: 16.1–29.4). The patients with CN had a median OS of 22.9 months (95% CI: 16.3–29.4), while those without CN had a median OS of 8.1 months (95% CI: 5.6–10.5) (p = 0.104). In the multivariate analysis, CN [hazard ratio (HR): 0.521; 95% CI: 0.297–0.916; p = 0.024] and the IMDC risk score (p = 0.011) were statistically significant factors affecting TTD; however, the IMDC risk score (p = 0.006) was the only significant factor for overall survival. Conclusions: Our study showed that the TTD of nivolumab was longer in metastatic ccRCC patients who underwent cytoreductive nephrectomy.